2020
DOI: 10.2196/23173
|View full text |Cite
|
Sign up to set email alerts
|

A Data Visualization and Dissemination Resource to Support HIV Prevention and Care at the Local Level: Analysis and Uses of the AIDSVu Public Data Resource

Abstract: Background AIDSVu is a public resource for visualizing HIV surveillance data and other population-based information relevant to HIV prevention, care, policy, and impact assessment. Objective The site, AIDSVu.org, aims to make data about the US HIV epidemic widely available, easily accessible, and locally relevant to inform public health decision making. Methods AIDSVu develops visualizations, maps, and downl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
65
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 102 publications
(87 citation statements)
references
References 15 publications
(27 reference statements)
0
65
0
Order By: Relevance
“…A previous analysis of the uses of data from an HIV dashboard [ 7 ] suggested that the examination of local data can lead directly to public health responses that are informed by the geographic areas or populations at highest risks for poor outcomes [ 8 ]. Prior uses of comparative geographic data on morbidity and service locations have led to the development of programs that geographically focus on new resources for prevention or care services [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous analysis of the uses of data from an HIV dashboard [ 7 ] suggested that the examination of local data can lead directly to public health responses that are informed by the geographic areas or populations at highest risks for poor outcomes [ 8 ]. Prior uses of comparative geographic data on morbidity and service locations have led to the development of programs that geographically focus on new resources for prevention or care services [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, the EHE initiative requires the effective use of data to identify baseline levels of new HIV infections, establish 5-year and 10-year goals for reductions in transmissions, monitor interim progress toward these goals, and provide the jurisdictions responsible for public health with tools to easily illustrate progress and areas of opportunities to local prevention providers and stakeholders. Although existing online tools provide access to HIV surveillance and related data in graphical and tabular formats [ 6 , 7 ], the existing tools are not specific to the EHE initiative and are not organized around either the explicit goals of EHE, the EHE jurisdictions, or the 4 EHE key strategies. Further, experience with other dashboard tools suggests that the mechanisms by which dashboards can promote changes in public health programs include the opportunity for a comparative assessment of indicators among jurisdictions [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…For pharmacists (n=10) and technicians (n=10), all pharmacies in the highest HIV zip code in Atlanta, as shown by AIDSVu, were identified. AIDSVu is an online, interactive display of HIV prevalence across the US [ 33 ]. Using an existing list of all pharmacies in the state of Georgia obtained from the Georgia Board of Pharmacy, we generated a list of pharmacies from high HIV zip codes and then randomly called each pharmacy to determine whether pharmacists or technicians were interested in participating in the study.…”
Section: Methodsmentioning
confidence: 99%
“…6 Southern US states, where 38% of the US population live, 7 are especially impacted: the south accounted for over half of all new HIV diagnoses in 2018. 7,8 Eight of the 12 states that have not yet expanded Medicaid are in the south, 9 underscoring overlapping public health crises of ongoing HIV transmission and insufficient political will to expand coverage for health care.…”
Section: Hiv In the Usa: Priorities For The New Administrationmentioning
confidence: 99%